Enhanced upward heat transport at deep submesoscale ocean fronts - Siegelman, Lia; Klein, Patrice; Riviere, Pascal; Thompson, Andrew F.; Torres, Hector S.; Flexas, Mar; Menemenlis, Dimitris (Nature Geoscience, 2020)
International audience The ocean is the largest solar energy collector on Earth. The amount of heat it can store is modulated by its complex circulation, which spans a broad range of spatial scales, from metres to thousands of kilometres. In the classical paradigm, fine oceanic scales, less than 20 km in size, are thought to drive a significant downward heat transport from the surface to the ocean interior, which increases oceanic heat uptake. Here we use a combination of satellite and in situ observations in the Antarctic Circumpolar Current to diagnose oceanic vertical heat transport. The results explicitly demonstrate how deep-reaching submesoscale fronts, with a size smaller than 20 km, are generated by mesoscale eddies of size 50-300 km. In contrast to the classical paradigm, these submesoscale fronts are shown to drive an anomalous upward heat transport from the ocean interior back to the surface that is larger than other contributions to vertical heat transport and of comparable magnitude to air-sea fluxes. This effect can remarkably alter the oceanic heat uptake and will be strongest in eddy-rich regions, such as the Antarctic Circumpolar Current, the Kuroshio Extension and the Gulf Stream, all of which are key players in the climate system.